Exploring the potential of extracellular matrix modulation to modify oral biofilm architecture - Narinder singh; Adarsh Anand; Priyanka Garg; Palwinder Kaur; Palakurthi yanadaiah; Md. Abubakar; Nitesh Kumar; Vancha harish; Sehajdeep saini (Molecular Biology Reports, 2026)

Rapid and visually interpretable LAMP assay for detection of pathogenic Pseudomonas aeruginosa in artificial sputum - Shukla Banerjee; Sukesh Kumar Bajire; Adarsh B. Mynalli; Rajesh P. Shastry (Molecular Biology Reports, 2026)

Evaluating potential GLOF threat to hydropower projects and communities in transboundary region of Eastern Himalaya - Sanjay Kumar Dwivedi; Adarsh Padhi; Ajanta Goswami; Tana Tage; Parmanand Sharma (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Alginate-aerogel-framework integrated with bismuth oxyhalide-based Z-scheme heterostructure for the photocatalytic degradation of ofloxacin: Mechanistic insights and machine learning modeling - Adarsh Singh; Anish Behuray; Ashok Kumar Gupta (Chemical Engineering Journal, 2026)

Trigonelline, a natural alkaloid, mitigates nanoplastic-induced neurotoxicity by restoring mitochondrial function and redox homeostasis in Drosophila melanogaster - Priya Rathor; Ashutosh K. Tiwari; Adarsh Kumar; Anurag Mathur; Abha Meena; Sheetal Rana; Ratnasekhar CH (Food and Chemical Toxicology, 2026)

Innovative Solutions for Micropollutant Removal in Wastewater: A Review of Current Challenges and Technological Advances - Devanshi Srivastava; Adarsh Kumar Arya (Water, Air, & Soil Pollution, 2026)

Comprehensive analysis of phytoconstituents in aerial organs of the vulnerable medicinal plant, Stereospermum colais (Buch.-Ham. ex Dillwyn) Mabb. - Vibha Pandey; Mohd. Ashraf; Amit Kumar; Prasanna Dutta; Adarsh Tripathi; Abhishek Niranjan; Debasis Chakrabarty (Natural Product Research, 2026)

Microbial-mediated phosphorus management under zero-tillage enhances maize productivity, P-use efficiency, and carbon management in a maize-wheat system - Amit Kumar; U.K. Behera; Shivadhar; Subhash Babu; Raghavendra Singh; Saurav Saha; Anil K. Choudhary; Adarsh Kumar; Gaurendra Gupta; B.A. Gudade; Anup Das; Vijay Singh Meena; et al. (Field Crops Research, 2026)

Advancing technologies for lignin-based jet fuel production in aqueous phase - Shivam Rawat; Adarsh Kumar; Shuaishuai Ma; Zhibin Yang; Rafal Gieleciak; Eric C.D. Tan; Joshua Heyne; Hongliang Wang; Thallada Bhaskar; Bin Yang (Chemical Engineering Journal, 2026)

Current status and challenges of biomanufacturing in India: a comprehensive review - Dhirendra Kumar; Ankush Yadav; Adarsh Kumar Shukla; Richa Tandon; Anshu Baldia; Deepanshi Rajput; Rubi Sheoran; Ahmed E. Abdel Aziz; Kashyap Kumar Dubey (Systems Microbiology and Biomanufacturing, 2026)

Trade-offs and synergies of conservation agriculture practices in the maize–wheat system: Improving yield, profitability, and soil resilience in a changing climate - Mohammad Hasanain; V.K. Singh; S.S. Rathore; Vijay Singh Meena; R.K. Singh; Kapila Shekhawat; B.S. Dwivedi; P.K. Upadhyay; Sunita Kumari Meena; Amit Kumar; Adarsh Kumar; Gaurav Verma; et al. (Field Crops Research, 2026)

OGTCN-E-MGO: an optimized deep learning framework for EEG-based schizophrenia detection - V. Milner Paul; Adarsh V. Parekkattil; Devika S. Kumar; Jijo Francis; Lal D. V. Nair; T. Jarin; Loitongbam Surajkumar Singh; Shuma Adhikari (Physical and Engineering Sciences in Medicine, 2026)

Synthesis of Diosgenin by Pseudomonas aeruginosa D3, an Endophyte of Dioscorea bulbifera - Krishna Nanda Dhal; Pramod Kumar Sahu; Amrita Gupta; Adarsh Kumar; Zaryab Shafi; Parul Johri; Sushma Mishra; Alok Kumar Srivastava (Current Microbiology, 2026)

Implication of chemical pattern recognition method for quality control of Boerhavia diffusa L. in Indian markets using RP-HPLC fingerprint - Mridul Kant Chaudhary; Ankita Misra; Adarsh Tiwari; Sanjeev Kumar Lale; Nagayya Shiddamallayya; Rabinarayan Acharya; Sharad Srivastava (Natural Product Research, 2026)

Thermally Stressed Solid-State Stability of Semaglutide: Understanding the Influence of Temperature on Protein Content, Secondary Structure, Phase Transition, and Chemical Degradation - Sideequl Akbar; Adarsh Malgave; Anumol Joseph; Ankit Kumar; Rajkumar Malayandi (Pharmaceutical Research, 2026)

Influence of pH, Buffering Capacity, Ionic Strength, Bile Salts, and Model Drugs on Micellization Behaviour of Salcaprozate Sodium in Physiological Range pH Buffers - Sideequl Akbar; Anumol Joseph; Adarsh Malgave; Ankit Kumar; Priyambada Bej; Rajkumar Malayandi (AAPS PharmSciTech, 2026)

Incorporation of network pharmacology, molecular docking, survival, density functional theory, and experimental studies to explore the potential key targets of formononetin by TERT-mediated anti-cancer effects in MCF-7 breast cancer - Rohit Singh Negi; Amit Kumar Singh; Adarsh Kumar Pathak; Rakesh Kumar Gupta; Nitish Kumar; Jyotirmayee Behera; Manjeet Kumar Sah Gond; Anand Kumar Singh; Pawan Kumar Dubey; Sunil Kumar Mishra (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Engineered self-sterilizing face masks via silver nanowire-microparticle composite ink printed on fabrics - Adarsh Sivan Pillai; Harris Varghese; Velayudhanpillai Prasannakumari Adarsh; Anoop Puthiyamadam; Sumith Sudhakar; Rajeev Kumar Sukumaran; Achu Chandran; Surendran Kuzhichalil Peethambharan (Chemical Engineering Journal, 2026)

Genetic and genomic resources of Vigna species for their utility in advanced breeding - Kuldeep Kumar; Sudhir Kumar Jha; B. Manu; Adarsh Kumar; Vaibhav Kumar; Khela Ram Soren; Meenal Rathore; Sandhya Sharma; Kishor Gaikwad (Biologia Futura, 2026)

Optimized computational framework for hydrogen blending in natural gas pipeline networks: analyzing hydrogen injection algorithms and operational parameters - Devanshi Srivastava; Adarsh Kumar Arya; Murali Pujari; Bhalchandra Shingan (Clean Technologies and Environmental Policy, 2026)

Genome-wide identification and expression analysis of UDP-glycosyltransferases genes associated with secondary metabolism during grain development in pearl millet (Pennisetum glaucum) - Adarsh Kumar; Theint Theint Tun; Vinay Kumar (Plant Gene, 2025)

Long term (2003–2023) analysis of Black Carbon aerosols and its impact on cloud characteristics over a highly polluted Delhi mega city of India - Lakshmi; Rashmi Deshwal; Vijay Kumar Soni; Adarsh Kumar (Atmospheric Environment, 2025)

Soil Moisture Prediction Using Artificial Neural Networks and Remote Sensing Data - Aryan Singh; Avdhesh Kumar; Ankit Singh; Rohit Kumar Tiwari; Navin Chaurasiya; Adarsh Singh; Shashank Shekhar Singh; Manish Pratap Singh (Remote Sensing in Earth Systems Sciences, 2025)

Computational identification of micro-nutrient (iron and zinc) deficiency related miRNAs and their targets in foxtail millet (Setaria italica) - K. Siddaardha Duggirala; Surbhi Panwar; Adarsh Kumar Shukla; Raushan Kumar Jha; Prasun Choudhary; Ashwani Kumar (Vegetos, 2025)

Exploring the Therapeutic Landscape of Probiotics in Enteric and Respiratory Viral Infections - Yashpal Singh Malik; Aakriti Pathania; Ujjwal Kumar De; Manu M.; Harsh Panwar; Jaspreet Kaur; Adarsh Mishra; Naveen Kumar; Souvik Ghosh; Varun Kumar Sarkar; Sakshi (Probiotics and Antimicrobial Proteins, 2025)

The Effects of Alpha Linolenic Acid (Omega-3 Fatty Acid) on Tobacco Craving Intensity, Withdrawal Symptoms and Biochemical Markers in Tobacco Users - Anjali Singh; Narsingh Verma; Surya Kant; Ajay Kumar Verma; Adarsh Tripathi; Kshitij Bhardwaj (Indian Journal of Clinical Biochemistry, 2025)

Digisonde based inter-analysis of ionospheric TEC during the major solar eclipse of 8 April 2024 over North/South American sites - Lakshmi; Vijay Kumar Soni; Adarsh Kumar (Advances in Space Research, 2025)

Pharmacognostical studies of the leaf and stem of Tetrastigma leucostaphylum (Dennst.) Alston ex Mabb. with special reference to soil chemistry - Stephy P. P.; Prasobh K. Mohan; Adarsh Krishna T.P.; Ajeesh Krishna T.P.; Selva Kumar S.; Walter Christhuraj C.; Soosai Raj S. (Vegetos, 2025)

Double zero-tilled bed-planting and optimized P-fertilization in maize-wheat rotation: An empirical investigation on root architecture, carbon-phosphorus dynamics, and soil carbon pools - M.N. Harish; Anil K. Choudhary; Anchal Dass; V.K. Singh; G.A. Rajanna; R.S. Bana; V. Paramesh; T. Varatharajan; Ingudam Bhupenchandra; R. Sadhukhan; Adarsh Kumar; K.S. Sachin; et al. (Journal of Environmental Management, 2025)

Computational simulations aided prioritization of genomic targets for congenital heart disease (CHD) against developmental toxicity - Adarsh Kumar Shukla; Prachi Kukshal (Reproductive Toxicology, 2025)

Relocation of major earthquakes in India from 1905 to 2011 using a non-linear probabilistic approach - Rinku Mahanta; Vipul Silwal; Adarsh Dwivedi; Vipin Kumar Maurya; C.P. Rajendran (Journal of Asian Earth Sciences, 2025)

Bacterial composition of dust deposited in Qatar: A seasonal study - Ramya Ramadoss; Adarsh Kumar Nishad; Balasubramanian Moovarkumudalvan; Basem Shomar (Science of The Total Environment, 2025)

Phenotypic Diversity in Stress-induced Childhood-Onset Neurodegeneration with Variable Ataxia and Seizures: Novel Associations with Parkinsonism, Icthyosis and Cataract - Jayakumari Nandana; Alfiya Fasaludeen; Adarsh Anil Kumar; Asish Vijayaraghavan; Sruthi S. Nair; Ajith Cherian; Ramshekhar N. Menon; Soumya Sundaram (The Cerebellum, 2025)

Advancing anammox pathways for wastewater treatment: A focus on conventional carrier challenges and innovations of 3D printed biocarrier - Veeravalli Preetham; Adarsh Singh; Chandra Sekhar Tiwary; Ashok Kumar Gupta (Journal of Environmental Chemical Engineering, 2025)

Temporal Effects of Conservation Agriculture-Based Rice–Wheat Cropping System on Soil Aggregation and Organic Carbon Dynamics in Northwestern Indo-Gangetic Plains - Amit K. Dash; Mahesh C. Meena; Shrila Das; Abir Dey; Md. Basit Raza; Saloni Tripathy; Adarsh Kumar; Dibyajyoti Panda; Adarsha Divyadarshan (Journal of Soil Science and Plant Nutrition, 2025)

Impact of the COVID-19 lockdown on zonal variability of lightning activity over the Indo-Gangetic Plains - Jeni Nepolian Victor; Adarsh Dube; Devendraa Siingh; Adarsh Kumar Kamra (Environmental Science and Pollution Research, 2025)

Computational insights into maternal environmental pollutants and folate pathway regulation - Adarsh Kumar Shukla; Shadab Ahamad; Prachi Kukshal (Reproductive Toxicology, 2025)

Catalytic conversion of paper sludge carbohydrates to jet fuel range hydrocarbons: Process optimization and techno-economic analysis - David Cruz; Hyeonji Park; Phoenix Tiller; Adarsh Kumar; Ronalds Gonzalez; Ashutosh Mittal; David K. Johnson; Sunkyu Park (Chemical Engineering Journal, 2025)

Modelling traffic noise-induced annoyance at intersections and its association with psychological health - Adarsh Yadav; Manoranjan Parida; Pushpa Choudhary; Brind Kumar (Transportation Research Part D: Transport and Environment, 2025)

Design, Development and Evaluation of Foot-Operated Sugarcane Sett Cutter - T. Mohanaselvan; S. P. Singh; Adarsh Kumar; H. L. Kushwaha; Susheel Kumar Sarkar; Pratibha Joshi (Sugar Tech, 2025)

Characterization of Alternaria Species Associated with Blight Disease of Edible Zucchini (Cucurbita Pepo L.) in India - Adarsh Kumar; Varnika Rana; Rupesh Bhardwaj; Theint Theint Tun; Vinay Kumar (Journal of Crop Health, 2025)

Understanding the Effects of Ash Content on Various Pretreatment Technologies for the Bioconversion of Corn Stover - Fitria; Adarsh Kumar; Libing Zhang; Jian Liu; Widya Fatriasari; Bin Yang (BioEnergy Research, 2025)

Ultrasound-assisted synthesis of a novel type-II Bi12O15Cl6/CTF-1 heterojunction for visible-light-driven photocatalytic degradation of levofloxacin: Reaction kinetics, degradation pathways, and toxicity assessment - Adarsh Singh; Amit Bhatnagar; Ashok Kumar Gupta (Journal of Environmental Chemical Engineering, 2024)

Sustainable phase change material developments for thermally comfortable smart buildings: A critical review - Aman Yadav; Mahendran Samykano; Adarsh Kumar Pandey; Sendhil Kumar Natarajan; Gopi Vasudevan; Guna Muthuvairavan; Subbarama Kousik Suraparaju (Process Safety and Environmental Protection, 2024)

Crop establishment and nutrient management options: Optimizing productivity, maximize profitability and mitigating adverse climatic conditions in the maize-based production system of Northwest India - Mohammad Hasanain; V.K. Singh; S.S. Rathore; Vijay Singh Meena; Sunita Kumari Meena; Kapila Shekhawat; R.K. Singh; B.S. Dwivedi; Raghavendra Singh; Subhash Babu; P.K. Upadhyay; Amit Kumar; et al. (Field Crops Research, 2024)

Virtual screening of potential orally active anti-bacterial compounds of finger millet - Raushan Kumar Jha; Adarsh Kumar Shukla; Anita Kumari; Ashwani Kumar (Vegetos, 2024)

Dietary biochar effect on growth performance, proximate composition, and physiological response of Penaeus vannamei (Boone, 1931) cultured in inland saline groundwater - Arun Konduri; Vidya Shree Bharti; Sreedharan Krishnan; Saurav Kumar; Satya Prakash Shukla; Narottam Prasad Sahu; Ajay Adarsh Rao Manupati; Tao Kara; Chalungal Thampi Amal (Animal Feed Science and Technology, 2024)

First report of cotton leaf curl multan virus infecting petunia in India - Varnika Rana; Adarsh Kumar; Tamanna Sihag; Sudesh Kumar Yadav; Vinay Kumar (Journal of Plant Pathology, 2024)

Multi-modal medical image fusion using improved dual-channel PCNN - Adarsh Sinha; Rahul Agarwal; Vinay Kumar; Nitin Garg; Dhruv Singh Pundir; Harsimran Singh; Ritu Rani; Chinmaya Panigrahy (Medical & Biological Engineering & Computing, 2024)

Sustainable Soil Management for Climate Resilience: Long-Term Management Effects on Soil Carbon Sequestration and Nitrogen Dynamics in a Semi-Arid Tropical Inceptisol of India - Debashis Dutta; Amrit Lal Meena; Chandra Bhanu; PC Ghasal; Jairam Choudhary; Sunil Kumar; RP Mishra; MA Ansari; Raghavendra KJ; AK Prusty; P. C. Jat; Poonam Kashyap; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Enhancing Sustainability and Productivity of Rice–Wheat-Green Gram Cropping System through Alternative Tillage and Crop Establishment Approaches in North-Bihar - Anupam Adarsh; Tarun Kumar; Kajol Kumari; Rajnesh Singh; Madhu Sudan Kundu; Ratnesh Kumar Jha; Jitendra Prasad; Anupma Kumari; Tej Pratap; Ravindra Kumar Tiwari (International Journal of Plant Production, 2024)

Catalytic activity of Zr/CeO2-Al2O3 catalyst for diesel soot oxidation: synthesis, characterization, and performance evaluation - Mritunjay Kumar Shukla; Vibhuti Bangwal; Atul Dhar; Thallada Bhaskar; Adarsh Kumar (Environmental Science and Pollution Research, 2024)

Identification of micronutrient deficiency related miRNA and their targets in Triticum aestivum using bioinformatics approach - Surbhi Panwar; Sunita Pal; Adarsh Kumar Shukla; Ashwani Kumar; Pradeep Kumar Sharma (Ecological Genetics and Genomics, 2024)

Effect of processing techniques on functional, antioxidants, and structural properties of finger millet (Eleusine coracana) flour - Arzoo; Neeru; Adarsh Kumar Shukla; Surbhi Panwar; Ashwani Kumar (Food and Humanity, 2024)

Nutritional evaluation of probiotics enriched rabadi beverage (PERB) and molecular mapping of digestive enzyme with dietary fibre for exploring the therapeutic potential - Prakash Yadav; Adarsh Kumar Shukla; Deepika; Neeru; Anita Kumari; Tejpal Dhewa; Ashwani Kumar (Food and Humanity, 2024)

Waste-derived thermal storage solutions for sustainable solar desalination using discarded engine oil and paraffin wax: A techno-environmental feasibility evaluation - Subbarama Kousik Suraparaju; Mahendran Samykano; Sendhil Kumar Natarajan; Reji Kumar Rajamony; Adarsh Kumar Pandey (Desalination, 2024)

Mechanization Level and Occupational Health Hazards in Sugarcane Cultivation in India - T. Mohanaselvan; S. P. Singh; Adarsh Kumar; H. L. Kushwaha; Susheel Kumar Sarkar; Pratibha Joshi (Sugar Tech, 2024)

Traffic noise modelling at intersections in mid-sized cities: an artificial neural network approach - Adarsh Yadav; Manoranjan Parida; Pushpa Choudhary; Brind Kumar; Daljeet Singh (Environmental Monitoring and Assessment, 2024)

Control of microstructural and mineralogical characteristics on thermo-elastic behaviour of coal-bearing sandstone under mild to high-temperature regimes: Experimental investigation and development of AI prediction models - Adarsh Tripathi; Ajeet Kumar Verma; Ashok Kumar Singh; Anindya Pain; Nachiketa Rai; Amit Kumar Verma (Journal of Earth System Science, 2024)

Productivity, soil health, and carbon management index of soybean-wheat cropping system under double zero-tillage and natural-farming based organic nutrient management in north-Indian plains - Gaurav Verma; A.K. Dhaka; Bhagat Singh; Adarsh Kumar; Anil K. Choudhary; Amit Kumar; Navish K. Kamboj; Mohammad Hasanain; Sachin Singh; Ingudam Bhupenchandra; Shabnam; Priyanka Sanwal; et al. (Science of The Total Environment, 2024)

Synergistic effect of biochar and plant growth promoting bacteria improve the growth and phytostabilization potential of Sorghum bicolor in Cd and Zn contaminated soils - Vadivel Anbuganesan; Ramasamy Vishnupradeep; Ninu Mehnaz; Adarsh Kumar; Helena Freitas; Mani Rajkumar (Rhizosphere, 2024)

Investigating important and necessary conditions to analyse traffic noise levels at intersections in mid-sized cities - Adarsh Yadav; Manoranjan Parida; Pushpa Choudhary; Brind Kumar (Journal of Environmental Management, 2024)

Oxidative treatment of micropollutants present in wastewater: A special emphasis on transformation products, their toxicity, detection, and field-scale investigations - Adarsh Singh; Abhradeep Majumder; Duduku Saidulu; Animesh Bhattacharya; Amit Bhatnagar; Ashok Kumar Gupta (Journal of Environmental Management, 2024)

Variations in GNSS-/GPS-Measured Ionospheric TEC and Solar Wind Plasma Parameters During the Total Solar Eclipse of 09 March 2016 - Lakshmi Dagar; Vijay Kumar Soni; Adarsh Kumar (Journal of the Indian Society of Remote Sensing, 2024)

Two decadal (2003–2022) based trend analysis of aerosol optical depth (AOD) and its impact on cloud properties over a highly polluted region of India - Lakshmi; Vijay Kumar Soni; Adarsh Kumar (Arabian Journal of Geosciences, 2024)

Development of sulfonated carbon-based solid-acid catalysts derived from biorefinery residues and biomass ash for xylan hydrolysis - Fitria; Adarsh Kumar; Martinus Dewa; Jian Liu; Su Ha; Bin Yang (Bioresource Technology Reports, 2023)

Assessments of occupational health hazards of tobacco farmworkers in Andhra Pradesh, India - Achugatla Kesav Kumar; Adarsh Kumar; Ramasubramanian Vaidhyanathan; Hari Lal Kushwaha; Debashis Chakraborty; Bhopal Singh Tomar (Toxicology and Environmental Health Sciences, 2023)

Rethinking underutilized cereal crops: pan-omics integration and green system biology - Mohammed Saba Rahim; Vinita Sharma; Pragati Yadav; Afsana Parveen; Adarsh Kumar; Joy Roy; Vinay Kumar (Planta, 2023)

Nanotechnology-integrated phase change material and nanofluids for solar applications as a potential approach for clean energy strategies: Progress, challenges, and opportunities - Zafar Said; Maham Aslam Sohail; Adarsh Kumar Pandey; Prabhakar Sharma; Adeel Waqas; Wei-Hsin Chen; Phuoc Quy Phong Nguyen; Van Nhanh Nguyen; Nguyen Dang Khoa Pham; Xuan Phuong Nguyen (Journal of Cleaner Production, 2023)

Nano-engineered silver rods from Pleurolobus gangeticus root extract and their antilithiatic and cytoprotective role on oxalate injured renal epithelial cells - Prasobh K. Mohan; T.P. Adarsh Krishna; P.P. Stephy; A. Thirumurugan; T. Senthil Kumar; B.D. Ranjitha Kumari (Biocatalysis and Agricultural Biotechnology, 2023)

Comparative study between antiviral drugs and natural compounds against “Cryo-EM structure of the SARS-CoV-2 Omicron spike” - Adarsh Kumar Shukla; Ashwani Kumar (Vegetos, 2023)

Integrated LIBS-Raman spectroscopy: A comprehensive approach to monitor microplastics and heavy metal contamination in water resources - P.S. Vaisakh; U.K. Adarsh; K. Amrutha; Anish Kumar Warrier; V.B. Kartha; V.K. Unnikrishnan (Environmental Research, 2023)

Optimizing the removal of calcium and magnesium from synthetic reverse osmosis concentrate using functional polyketones: A combined experimental and machine learning approach - Muhammad Yaqub; Adarsh Kumar; Wontae Lee (Journal of Water Process Engineering, 2023)

Performance assessment of photo-controlled catalytic and moving biocarrier-based hybrid systems for the treatment of pharmaceuticals from municipal and industrial wastewater: Insights into influencing factors and degradation mechanisms - Bramha Gupta; Duduku Saidulu; Ashish Srivastava; Akash Rawat; Adarsh Singh; Amit Bhatnagar; Ashok Kumar Gupta (Journal of Environmental Chemical Engineering, 2023)

Development and application of recombinase polymerase amplification for rapid detection of rice false smut pathogen (Ustilaginoidea virens) - Amrita Banerjee; M.K. Bag; Adarsh Kumar Chandra; Somnath Roy; S. Raghu; N.P. Mandal (Crop Protection, 2023)

Tetrapods based engineering of organic phase change material for thermal energy storage - Kalidasan Balasubramanian; Adarsh Kumar Pandey; Reza Abolhassani; Horst-Günter Rubahn; Saidur Rahman; Yogendra Kumar Mishra (Chemical Engineering Journal, 2023)

Performance evaluation of external compound parabolic concentrator integrated with thermal storage tank for domestic solar refrigeration system - Sathiya Satchi Christopher; Amrit Kumar Thakur; Soumya Kanti Hazra; Swellam Wafa Sharshir; Adarsh Kumar Pandey; Saidur Rahman; Punit Singh; Lingala Syam Sunder; Arun Kumaradas Raj; Ramasamy Dhivagar; Ravishankar Sathyamurthy (Environmental Science and Pollution Research, 2023)

Phytomitigation potential and adaptive responses of helophyte Typha latifolia L. to copper smelter-influenced heavily multi-metal contamination - Gregory Shiryaev; Maria Maleva; Galina Borisova; Tripti; Olga Voropaeva; Adarsh Kumar (Environmental Science and Pollution Research, 2023)

Multi-disciplinary engineering design of a high-speed nature-inspired unmanned aquatic vehicle - Vijayanandh Raja; Arul Prakash R; Adarsh Kumar; Diego A. de J. Pacheco (Ocean Engineering, 2023)

Unveiling the climatic origin of streamflow persistence through multifractal analysis of hydro-meteorological datasets of India - Aggie Suman; Archana Devarajan Sindhu; Aruna Kumar Nayak; Adarsh Sankaran Namboothiri; Basudev Biswal (Hydrological Sciences Journal, 2023)

Constructed wetlands for the removal of pharmaceuticals and personal care products (PPCPs) from wastewater: origin, impacts, treatment methods, and SWOT analysis - Saroj Kumar; Bhanu Pratap; Divya Dubey; Adarsh Kumar; Saurabh Shukla; Venkatesh Dutta (Environmental Monitoring and Assessment, 2022)

Sole- or Dual-Crop Basis Residue Mulching and Zn Fertilization Lead to Improved Productivity, Rhizo-modulation and Soil Health in Zero-Tilled Pigeonpea–Wheat Cropping System - Adarsh Kumar; K. S. Rana; Anil K. Choudhary; R. S. Bana; V. K. Sharma; Gaurendra Gupta; Sudhir K. Rajpoot; Ingudam Bhupenchandra; Mukesh Choudhary; Praveen Jakhar; Amit Kumar; Abhishek Kumar; et al. (Journal of Soil Science and Plant Nutrition, 2022)

Synthesis and characterization of zinc derivatized 3, 5-dihydroxy 4′, 7-dimethoxyflavone and its anti leishmaniasis activity against Leishmania donovani - Manish Kumar Gupta; Adarsh Kumar Chiranjivi; Tanmay Dutta; Vikash Kumar Dubey; Latha Rangan (BioMetals, 2022)

Diversity of Bacterial Endophytes of Maize (Zea mays) and Their Functional Potential for Micronutrient Biofortification - Shaloo Verma; Murugan Kumar; Adarsh Kumar; Sudipta Das; Hillol Chakdar; Ajit Varma; Anil Kumar Saxena (Current Microbiology, 2022)

Success of microbial genes based transgenic crops: Bt and beyond Bt - Jyotsana Tilgam; Kuldeep Kumar; Deepanshu Jayaswal; Sharani Choudhury; Adarsh Kumar; Kuldip Jayaswall; Anil Kumar Saxena (Molecular Biology Reports, 2021)

Effect of boron supplementation on laying performance of White Leghorn hens fed diet with and without adequate level of calcium - Vijay Adarsh; Pal Dintaran; Gowda N. K. Shivakumar; Elangovan A. Vijayarangam; Dey Debpriyo Kumar; Kurni Nagaraj; Jadhav S. Eknath (Tropical Animal Health and Production, 2021)

Comparing the nutrient changes, heavy metals, and genotoxicity assessment before and after vermicomposting of thermal fly ash using Eisenia fetida - Bhawana Sohal; Sharanpreet Singh; Soubam Indra Kumar Singh; Sartaj Ahmad Bhat; Jagdeep Kaur; Jaswinder Singh; Adarsh Pal Vig (Environmental Science and Pollution Research, 2021)

Genetically modified crop regulations: scope and opportunity using the CRISPR-Cas9 genome editing approach - Shweta Gupta; Adarsh Kumar; Rupali Patel; Vinay Kumar (Molecular Biology Reports, 2021)

Nickel and copper accumulation strategies in Odontarrhena obovata growing on copper smelter-influenced and non-influenced serpentine soils: a comparative field study - Tripti; Adarsh Kumar; Maria Maleva; Galina Borisova; Nadezhda Chukina; Maria Morozova; Irina Kiseleva (Environmental Geochemistry and Health, 2021)

Effects of Elevated Temperatures on the Microstructural, Physico-Mechanical and Elastic Properties of Barakar Sandstone: A Study from One of the World’s Largest Underground Coalmine Fire Region, Jharia, India - Adarsh Tripathi; Noopur Gupta; Ashok Kumar Singh; Sarada P. Mohanty; Nachiketa Rai; Anindya Pain (Rock Mechanics and Rock Engineering, 2021)

Regional variability in lightning activity over South Asia - Adarsh Kumar Kamra; Penki Ramesh Kumar (International Journal of Climatology, 2021)
The regional variability of lightning activity over 10 different regions, selected with at least one major meteorological/topographical feature, of South Asia (8°N–36°N, 90°E–100°E) have been examined on all time scales from the data obtained from July 1995 to December 2013 from the Tropical Rainfall Measuring Mission satellite. A comparative study of the correlation coefficients calculated between lightning flash rate and convective parameters, aerosol optical depth (AOD) and topography for different regions is carried out. Impact of the progress of the Asian Monsoon on the spatio‐temporal variability of flash rate is also examined. Monthly‐averaged variations are annual at the regions >2,700 m in altitude and are semi‐annual at the regions Key Points Lightning flash rate in the South Asian regions is sensitive to the surface temperature and to the altitude in the Himalayas Progress of the Asian monsoon strongly impacts the regional distribution of the flash rate in the South Asia Long‐term changes in flash rate during 1995–2013 in the South Asian regions increased with the surface temperature and aerosols

Toxic metal(loid)s contamination and potential human health risk assessment in the vicinity of century-old copper smelter, Karabash, Russia - Adarsh Kumar; Tripti; Maria Maleva; Irina Kiseleva; Subodh Kumar Maiti; Maria Morozova (Environmental Geochemistry and Health, 2020)

Sugar cane Canopy Spraying: A Perspective Solution with Ergonomics and Mechatronics Approach - S. P. Singh; Adarsh Kumar; H. L. Kushwaha (Sugar Tech, 2020)

Distribution of lightning in relation to topography and vegetation cover over the dry and moist regions in the Himalayas - Sunil Oulkar; Devendraa Siingh; Upal Saha; Adarsh Kumar Kamra (Journal of Earth System Science, 2019)

Multifractal characterization of meteorological drought in India using detrended fluctuation analysis - S. Adarsh; D. Nagesh Kumar; B. Deepthi; G. Gayathri; S. S. Aswathy; S. Bhagyasree (International Journal of Climatology, 2019)
This study presents multifractal detrended fluctuation analysis (MF‐DFA) to describe the multifractality of Standardized Precipitation Index (SPI) series from 30 meteorological subdivisions of India estimated at different aggregation timescales (3, 6 and 12 months) based on long‐term monthly rainfall data sets of 1871–2016 period. The plots of fluctuation function and generalized Hurst exponents confirmed that multifractality is evident in most of the SPI series; however, it is found that its strength and persistency differ with timescale and space. The Hurst exponents of long‐term (SPI‐12) and medium‐term (SPI‐6) drought series of all subdivisions showed long‐term persistence irrespective of the climatic conditions of the region, while the short‐term droughts (SPI‐3) of six subdivisions displayed short‐term persistence. Further, the analysis by partitioning the data to four time spells: 1871–1905, 1906–1940, 1941–1975 and 1976–2016 showed that the persistency of long‐ and medium‐term drought is rather permanent. The analysis on changes in multifractal properties with respect to the climatic shift of 1976/1977 period showed that there is a clear increase in multifractal properties of all types of drought series in the recent past (post‐1976 period). This study also finds that the Hurst exponents and degree of multifractality of all types of droughts increase with increase in aggregation timescales. The multifractality of all the long‐term drought series (SPI‐12) and most of the SPI‐6 series are found to be due to correlation properties, while that of SPI‐3 is because of joint effect of correlation properties and the broadness of probability distribution.

Reclamation of coal mine spoil and its effect on Technosol quality and carbon sequestration: a case study from India - Jitendra Ahirwal; Adarsh Kumar; Marcin Pietrzykowski; Subodh Kumar Maiti (Environmental Science and Pollution Research, 2018)

In vitro efficacy of amitraz, coumaphos, deltamethrin and lindane against engorged female Rhipicephalus (Boophilus) annulatus and Haemaphysalis bispinosa ticks - Reghu Ravindran; Gopi Jyothimol; Krishnan Kavillimakkil Amithamol; Athalathil Ramankutty Sunil; Leena Chandrasekhar; Dibya Ranjan Lenka; Achuthkumar Amritha; Kanapadinchareveetil Sreelekha; Nanjundappa Sathish; Darsana Udayan; Thumadath Palayullaparambil Adarsh Krishna; Thirumangalath Meethal Divya; et al. (Experimental and Applied Acarology, 2018)

In vitro conservation of Alectra chitrakutensis: a critically endangered root parasitic plant of high medicinal importance - Shital Kailsh Sharma; Anita Patil; Adarsh Kumar Agnihotri; Shakti Mehrotra (Acta Physiologiae Plantarum, 2018)

Biodiversity variability and metal accumulation strategies in plants spontaneously inhibiting fly ash lagoon, India - Suchita Mukhopadhyay; Vivek Rana; Adarsh Kumar; Subodh Kumar Maiti (Environmental Science and Pollution Research, 2017)

Stabilization of tannery sludge amended soil using Ricinus communis, Brassica juncea and Nerium oleander - Poonam Rani; Adarsh Kumar; Ramesh Chandra Arya (Journal of Soils and Sediments, 2017)

Grasses and legumes facilitate phytoremediation of metalliferous soils in the vicinity of an abandoned chromite–asbestos mine - Adarsh Kumar; Subodh Kumar Maiti; Tripti; Majeti Narasimha Vara Prasad; Raj Shekhar Singh (Journal of Soils and Sediments, 2017)

Evaluation of practice effect on neuropsychological measures among persons with and without HIV infection in northern India - Raymond L. Ownby; Drenna Waldrop-Valverde; Deborah L. Jones; Sunil Sharma; Ritu Nehra; Adarsh M. Kumar; Sudesh Prabhakar; Amarilis Acevedo; Mahendra Kumar (Journal of NeuroVirology, 2017)

High dose of urea enhances the nickel and copper toxicity in Brazilian elodea (Egeria densa Planch. Casp.) - Maria Maleva; Galina Borisova; Nadezhda Chukina; Adarsh Kumar; Majeti Narasimha Vara Prasad (Brazilian Journal of Botany, 2016)

Neuropsychological test performance among healthy persons in northern India: development of normative data - Drenna Waldrop-Valverde; Raymond L. Ownby; Deborah L. Jones; Sunil Sharma; Ritu Nehra; Adarsh M. Kumar; Sudesh Prabhakar; Mahendra Kumar (Journal of NeuroVirology, 2015)

Cotton leaf curl Burewala virus with intact or mutant transcriptional activator proteins: complexity of cotton leaf curl disease - Jitendra Kumar; Samatha Gunapati; Anshu Alok; Adarsh Lalit; Rekha Gadre; Naresh C. Sharma; Joy K. Roy; Sudhir P. Singh (Archives of Virology, 2015)

Translocation and Bioaccumulation of Metals in Oryza sativa and Zea mays Growing in Chromite-Asbestos Contaminated Agricultural Fields, Jharkhand, India - Adarsh Kumar; Subodh Kumar Maiti (Bulletin of Environmental Contamination and Toxicology, 2014)

A new betasatellite associated with cotton leaf curl Burewala virus infecting tomato in India: influence on symptoms and viral accumulation - Jitendra Kumar; Samatha Gunapati; Sudhir P. Singh; Abhinav Kumar; Adarsh Lalit; Naresh C. Sharma; Rekha Puranik; Rakesh Tuli (Archives of Virology, 2013)

Human immunodeficiency virus infection in the CNS and decreased dopamine availability: relationship with neuropsychological performance - Adarsh M. Kumar; Raymond L. Ownby; Drenna Waldrop-Valverde; Benny Fernandez; Mahendra Kumar (Journal of NeuroVirology, 2011)

Education Effects on the International HIV Dementia Scale - Drenna Waldrop-Valverde; Ritu Nehra; Sunil Sharma; Ashima Malik; Deborah Jones; Adarsh M Kumar; Raymond L Ownby; Ajay Wanchu; Steve Weiss; Sudesh Prabhakar; Mahendra Kumar (Journal of NeuroVirology, 2010)

Tumor Necrosis Factor-alpha Levels in HIV-1 Seropositive Injecting Drug Users - Raymond L. Ownby; Adarsh M. Kumar; J. Benny Fernandez; Irina Moleon-Borodowsky; Louis Gonzalez; Seth Eisdorfer; Drenna Waldrop-Valverde; Mahendra Kumar (Journal of Neuroimmune Pharmacology, 2009)

Human immunodeficiency virus type 1 in the central nervous system leads to decreased dopamine in different regions of postmortem human brains - Adarsh M Kumar; JB Fernandez; Elyse J Singer; Deborah Commins; Drenna Waldrop-Valverde; Raymond L Ownby; Mahendra Kumar (Journal of NeuroVirology, 2009)

Human immunodeficiency virus type 1 RNA Levels in different regions of human brain: Quantification using real-time reverse transcriptase–polymerase chain reaction - Adarsh M Kumar; Irina Borodowsky; Benny Fernandez; Louis Gonzalez; Mahendra Kumar (Journal of NeuroVirology, 2007)

Bioactivity and structure–activity relationship of natural methoxylated phenylpropenes and their derivatives against Aphis craccivora Koch (Hemiptera: Aphididae) - Dhananjay Kumar Tewary; Anu Bhardwaj; Anuj Sharma; Arun Kumar Sinha; Adarsh Shanker (Journal of Pest Science, 2006)

Effect of coenzyme Q10 on risk of atherosclerosis in patients with recent myocardial infarction - Ram B. Singh; Narankar Singh Neki; Kumar Kartikey; Daniel Pella; Adarsh Kumar; Mohammad Arif Niaz; Amar Singh Thakur (Molecular and Cellular Biochemistry, 2003)